KONTRIBUSI SEKTOR KEHUTANAN TERHADAP PEREKONOMIAN WILAYAH: KASUS PROVINSI LAMPUNG - Sanudin, Sanudin; Awang, San Afri; Sadono, Ronggo; Purwanto, Dan Ris Hadi (Bumi Lestari, 2016)
One of economy growth indicator is Gross Regional Domestic Product (GRDP).  The research was aimed to know contribution of forestry sector to regional economy in Lampung Province.  Data used were GRDP and Gross Domestic Product (GDP) on 2000 constant market prices during 2004 to 2013 period.  Location Quotient (LQ), Multiplier Effect, and Shift Share Analysis (SSA) were used in this research.  The results showed that in the period 2004-2013, forestry sector is not a basic sector in Lampung Province with LQ value 0.18. Multiplier effect value of forestry sector is 94.92 which means that every additional income of Rp Y in the forestry sector will result in added revenue of 94.92 x Rp Y in agriculture sector.  Forestry sector GRDP contributed for 0.38 percent to regional economy of Lampung Province. National growth component of forestry sector in Lampung Province gives a positive effect to national growth.  Industrial mix component of forestry sector in Lampung Province is slower than national average.  Local share component has a positive value which means that the forestry sector in Lampung Province is competitive.
Keywords: forestry sector, contribution, economy regional, Lampung Province